Job stress among shift workers :a case study at Malaysia airports sdn. bhd. (MASB) Kuching - Nancy, Kok Fung Ling (Universiti Malaysia Sarawak, UNIMAS, 2008)
T his study focuses on the perceived level of job stress and the sources of job stress faced by the shift workers in Malaysia Airports Sdn. Bhd. (MASB) Kuching. There are three selected sources of stress in this study which are roled - based factor, relationship with others and the working environment. The study utilized a survey methodology. A total of 196 shift workers (61% of the total target population) from four departments were selected as the sampl e of this study through the use of random sampling method. T he overall results revealed that 75% of the respondents reported hav ing normal level of job stress, 14.3% having low level of job stress and 10.7 % having high level of job stress. The t - test analysis revealed that female workers tend to have higher level of stress compare to those male shift workers. Besides, the results of Pearson Correlation Coefficient Analysis also revealed that all of the three selected sources of job stress were significantly related to the perceived level of job stress. T here was a positive relationship between level of job stress and role - based sou rces (r = 0.7 91), relationship with others (r = 0. 702) and working environment (r = 0.6 52). As such, role - based factor can be seen as the main sources of job stress among the shift workers in MASB, Kuching. The management of the organization is recommend t o put special emphasis on this factor .